Are Ghettos Good or Bad? Evidence from U.S. Internal Migration - Junfu Zhang; Liang Zheng (Institute for the Study of Labor (IZA), 2014)
It is difficult to determine whether ghettos are good or bad, partly because racial segregation may have some effects that are unobservable. To overcome this challenge, we present a migration choice model that allows for estimating the overall effects of racial segregation. The key idea underlying our empirical approach is that if segregation indeed has a negative overall effect, migrants should be willing to give up some earnings to avoid living in segregated cities. Using decennial census data from 1980 to 2000, we provide new evidence that ghettos are bad. It is shown that both black and white migrants prefer to live in less segregated cities. For example, for a one-percentage-point reduction in the dissimilarity index, the estimated marginal willingness to pay of blacks is 436 (in 1999 dollars) in 2000. Among whites, this marginal willingness to pay is 301.
Keywords: O15; R12; R23; 330; residential segregation; internal migration; discrete choice model